(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This work examines the multifaceted challenges encountered during adolescence—a critical period marked by significant physical, emotional, and social changes. It explores common issues such as peer pressure, academic stress, and identity crises, while also addressing the impact of social media on self-esteem and body image. The discussion extends to mental health concerns, including anxiety and depression, which often arise from the overwhelming expectations placed on teenagers. Additionally, the work analyzes the dynamics of family conflicts and the struggle for independence that characterizes this stage of life. By synthesizing research and real-life examples, the annotation underscores the importance of supportive interventions from educators, parents, and mental health professionals to foster resilience and well-being among adolescents.